The nullity of the thing judged fruitful and the need for its modification in the Civil Procedural Code: Analysis of processes of the Superior Court of Justice of Tacna, period 2011-2013 - Juárez Ticona, Rosa Ivonne (2015)
Objective: The objective of the  research is to determine whether the  amendment of Article 178 of the  Peruvian Civil Code regarding the  annulment of fraudulent res judicata  is necessary. Method: Our study was set as one of  the explanatory type with dogmatic  character through the use of  scientific and analytical method. The  research design employed was the  cause - effect one purely  transactional descriptive research or  cross - correlational, within the  purpose of investigating the  relationships between variables that  were used in the investigation, the  problems and the theoretical  framework Of the same. The study  population was comprised of  professionals in judicial matters: Tax  (12), judges (13), Law (2400) and  University Teachers (75). 05  matchings review on Nullity of  fraudulent res judicata. Review  records on 07 Nullity of fraudulent  res judicata, 2011-2013.   Results: Nullity of fraudulent res  judicata; It is one single legal tool to  penetrate the scope of res judicata,  making permissible revision of  judgments in exceptional and  restrictive manner, based on the  specific grounds set out in Article  178 of the Civil Procedure Code,  therefore, by the above institute  does not It may challenge a final  decision on the format of a new  contesting means granted by law in  favor of the party who has exhausted  all procedural remedies and is not in  accordance with the ¡judgment  handed, but is rather a guarantee  supported by principles Justice,  applicable only in cases where fraud  or collusion precisely that it had  incurred, affecting the right to due  process; and, in such case, the  injured defendant had not been  informed promptly of such facts and /  or could not validly make use of the  defenses and remedies provided by  law; therefore, unlike other  processes, that of fraudulent res  judicata, it is decided on the  contested as fraudulent statement,  and it was founded, its effect is  purely rescissory, that is, declared  invalid the previous sentence, so  that The subject of debate is not the  substantial issue, but the conduct  described as dishonest, incurred by  the litigants, or the judge, or all of  them. Conclusion: civil review, it is one of  the mechanisms to attack fraudulent  conduct in judicial proceedings after  the judgment issued res judicata.  This figure, adjusted from Roman  law and collected in the Games, it  has to nullity of fraudulent res  judicata as one ofits species